'It's the simple things you do first that start the process of help': Undergraduate nursing and midwifery students' experiences of the Mental Health First Aid course. Issue 3 (June 2017) - Kelly, Jenny; Birks, Melanie
Summary: Background: Mental Health First Aid (MHFA) is the initial help offered to a person developing a mental health problem or experiencing a mental health crisis. The MHFA course is a 12 h evidence-based course which teaches members of the general public to provide first aid assistance until the crisis resolves or the individual receives professional help. While the MHFA program does not teach people to provide a diagnosis or treat mental health conditions, it has been established as an effective tool in improving mental health literacy, reducing stigma and increasing helping behaviours. Aim: The aim of the study was to explore the experiences of students who completed a tailored 13-h version of this MHFA course specifically developed for undergraduate nursing and midwifery students. Method: Sixty-six students, the majority of whom were female and aged 17–55 years, completed an online survey. The survey sought to explore the perspectives of students in respect of both undertaking the course as well as its value in retrospect. Areas explored in the survey included: relevance and value of content; strengths and weaknesses of the course; if and how they had applied any of the skills learnt and overall perceptions of the course. Results: Findings showed that the vast majority of students (86%) regarded the course as appropriate for nursing and midwifery students with 89% stating they would recommend the course to other university students. Conclusion: Data indicates that the course had application and impact following completion beyond what had been anticipated by the students. Responses to the open ended questions suggest widespread support for the routine offering of this course for beginning nursing and midwifery students nationwide.